The Social and Spiritual Support as Correlated Determinants of Elderly Happiness in Nursing Home - Randy Refnandes; Achir Yani S Hamid; Heppy Sasmita (Elevate, 2018)
Background: Some of the elderly appeared to live happily, but not a few of them experienced the opposite. Old age lived with a sequential of unhappiness lead to any discomfort due to the decline in physical function. It affected the elderly unable to carry out primary and daily activities. Purpose: The aimed of this research is to perceive the correlation social and spiritual support with the happiness of elderly in Sabai Nan Aluih Sicincin nursing home. Method: The study used descriptive correlation with cross sectional study design. The study was conducted at Tresna Werdha Sabai Nan Aluih nursing home Sicincin from 15 June to 11 July 2015. The population was 110 people with the sample of 82 respondents according required criteria. Results: The results showed the average of social support of elderly in Sabai Nan Aluih nursing home 21.23, SD=3,548. The spiritual support mean score 47.83, SD= 4,427. The mean score of happiness 63,01 with SD= 4,804. Bivariate analysis used Pearson Product Moment Correlation test, it was found that the correlation between social support and the happiness of the elderly, (p = 0,001), the spiritual correlation and the happiness of elderly (p = 0,000). Conclusion: Therefore, it is expected that the nursing home should be more concerned about the spiritual health of the respondents, by providing media such as television to watch spiritual specific TV program activities after the dawn prayer for the positive outcome expected